Holocene ice wedge formation in the Eureka Sound Lowlands, high Arctic Canada. (July 2021) - Campbell-Heaton, Kethra; Lacelle, Denis; Fisher, David; Pollard, Wayne
Abstract: Ice wedges are ubiquitous periglacial features in permafrost terrain. This study investigates the timing of ice wedge formation in the Fosheim Peninsula (Ellesmere and Axel Heiberg Islands). In this region, ice wedge polygons occupy 50% of the landscape, the majority occurring below the marine limit in the Eureka Sound Lowlands. Numerical simulations suggest that ice wedges may crack to depths of 2.7–3.6 m following a rapid cooling of the ground over mean winter surface temperatures of −18°C to −38°C, corresponding to the depth of ice wedges in the region. The dissolved organic carbon (DOC)/Cl molar ratios suggest that the DOC in the ice wedges is sourced from snowmelt and not from leaching of the active layer. Based on 32 14 CDOC measurements from 15 ice wedges, the wedges were likely developing between 9000–2500 cal yr BP. This interval also corresponds to the period of peat accumulation in the region, a proxy of increased moisture. Considering that winter air temperatures remained favorable for ice wedge growth throughout the Holocene, the timing of ice wedge formation reflects changes in snowfall. Overall, this study provides the first reconstruction of ice wedge formation from a high Arctic polar desert environment.